2007
DOI: 10.1002/sd.334
|View full text |Cite
|
Sign up to set email alerts
|

Determinant factors in the degree of implementation of Local Agenda 21 in the European Union

Abstract: The concern for sustainable development reached its greatest form of expression in what is known as the Brundtland Report; however, it was the Rio de Janeiro Conference of 1992 that created the foundations, through agreements such as Agenda 21. Though the success of Agenda 21 depends fundamentally on central governments, local administrations can play a decisive role, which is why European cities have taken on a serious commitment to enforce it by way of the Aalborg Charter. This paper evaluates the advancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 34 publications
1
29
1
Order By: Relevance
“…The scarce previous studies which have analysed this issue have found a negative influence of rightwing parties on the implementation of Local Agenda 21 (García-Sánchez and Prado-Lorenzo [5]). Nonetheless, there is not enough previous evidence that can predict which political tendency may be more prone to favouring local sustainability.…”
Section: Political Ideology and Stabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…The scarce previous studies which have analysed this issue have found a negative influence of rightwing parties on the implementation of Local Agenda 21 (García-Sánchez and Prado-Lorenzo [5]). Nonetheless, there is not enough previous evidence that can predict which political tendency may be more prone to favouring local sustainability.…”
Section: Political Ideology and Stabilitymentioning
confidence: 98%
“…This opposition is more important in cases of weak or fragmented governments, that is, those that lack an absolute majority and therefore cannot impose their decisions with only the votes of their own party. Moreover, certain political ideologies are more favourable to sustainable policies than others (García-Sánchez and Prado-Lorenzo [5]). …”
Section: Introductionmentioning
confidence: 99%
“…According to several studies [20][21][22][23][24][25], over fifteen years the number of LA21 processes at world level doesn't reach original expectations and its qualitative impact is limited. The different experiences, especially those in the European context as Europe is the most active region for LA21 (ICLEI [24]), make it possible to identify a series of difficulties and obstacles common to LA21 processes.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Below is a selection of said variables that will help to identify the factors influencing LA21 planning approaches. Based on [22,24,26,27], among others, LA21 presents the following difficulties and challenges: non existence of real interdisciplinarity at municipal level, giving rise to sector type adjustments which do not include an integral, interconnected vision of the problems; inadequate organisational structure at local government level; weak participative tradition and limited tradition of collective responsibility; insufficient investment (of economic, material and human resources) in the participative processes as opposed to other dimensions; many LA21 led by elected political representatives and even external agents (as private consultants); compelling and urgent need to resolve everyday problems demanded by citizens and stakeholders which detracts from the ability to reflect, debate, participate and plan; scanty contribution from social networks, especially business organisations; lack of political leadership and consensus in town councils, and short-term vision; decision-making on local issues taken at other levels, with no clear definition of the role of supramunicipal entities; lack of training for technical experts and politicians on sustainability issues; a planning and programming vocation based on an exhaustive diagnostic of the territory, with expert knowledge taking precedence over others (methodologies oriented at developing intangibles such as knowledge, social relations and empowerment are rarely applied); need for flexible implementation and monitoring systems.…”
Section: Lessons Learnedmentioning
confidence: 99%
See 1 more Smart Citation